Enhancing procedure of using new means of technologies in criminal proceedings - Magherescu, Delia (IUS ET SCIENTIA, 2020)
The new era of technology is currently of high interest for the judicial proceedings in criminal matters. Although digital technologies have been increased in the last decades, both legislator and judicial authorities being involved in developing more and more efficient means of forensic investigation in purpose to prevent and combat the criminal phenomena, the criminal organizations are also interested in breaking such legal digital framework and achieving their own scope - a financial one. On the one hand, they are permanently interested in committing serious crimes including those in digital environment, whose consequences are one of the most dangerous crimes for the entire contemporary society. On the other hand, the law enforcement agencies are working in close cooperation with experts in digital field in order to gather information on how to improve the situation itself and investigate the criminal activities by means of digital evidence. In this context, the digitalization is an efficient tool of providing information, data and other instruments the judicial bodies need in achieving their goals in criminal proceedings. The current paper focuses on the techniques and methods that judicial bodies use in the investigation activity of gathering digital evidence that may serve in making decision in criminal cases the judicial bodies are invested with. The paper is structured in five chapters, each of them providing referential elements on the proposed topic. Its structure is designed as follows: Introduction; Aims; Methodology of Research; Achievements and failures through using new technologies; Doctrinal and jurisprudence approach, and Conclusion section, which advances a de lege ferenda proposal.